Changes in hydration status of soccer players competing in the 2008 European Championship - Gatterer, H.; Schenk, K.; Ferrari, P.; Faulhaber, M.; Schopp, E.; Burtscher, M. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Body composition is highly modifiable through exercise and may be changed by the physical stress of soccer training and competition. Especially body water as a constituent of body composition is assumed to be subjected to changes. It is speculated that during the most important soccer championship the combination of heat and the strenuous competitive program could lead to the development of a chronic state of hypohydration. However, no one tested this hypothesis. Therefore, the purpose of present work was to investigate the impact of the European Soccer Championship 2008 on players` body composition. METHODS: Participants were 14 players of one team, split into Starters (N.=7) and Non-Starters (N.=7). Starters participated in the games, while Non-Starters served as substitutes, with marginal playing times. Body composition was examined by bioelectrical impedance analysis before the championship and 36 hours after the first and second game. RESULTS: After the first game, Starters and Non-Starters showed decreased extra-cellular mass (-3.3% and -5.5%) and body cell mass (-4.1% and -6.1%) compared to prechampionship measurements. The impedance vector graph showed a significant lengthening in both groups (Starters T²=30.5, P=0.000; Non Starters T²=39.0, P=0.000). After the second game, extra-cellular mass (-3.4%) and body weight (-1.1%) decreased in Starters only. ANOVA revealed a significant difference in extra-cellular mass between Starters and Non-Starters (P=0.027). The impedance vector graph was lengthened in the Starters only (T²=17.5, P=0.000). The distance covered during the games was correlated to the percent drop in extra-cellular mass between the end of games 1 and 2 (r=-0.602; P=0.023). CONCLUSION: Players competing in the European championship games experienced a decrease in extra-cellular mass and body weight. The impedance vector graph showed a lengthening, indicating fluid loss. Therefore, proper hydration of players requires diligent attention.